Formative Research as a Strategic Foundation of Public Relations in Digital News Media: A Case Study of Tribunnews - Fenty Fauziah Nur Islami; Ambang Priyonggo; Bertha Sri Eko Murtiningsih (Universitas Multimedia Nusantara, 2025)
In the digital era, mass media is required to adapt to changes in public information consumption behavior. Tribunnews, as one of the largest local news portals in Indonesia, faces the challenge of maintaining relevance and audience trust amidst intense competition. In response to this situation, Tribunnews has developed various public relations strategies to establish itself as a quality and trustworthy local media outlet. This research aims to analyze the public relations strategies implemented by Tribunnews. The research focus includes identifying the needs and expectations of the local audience, analyzing the main strategies used, evaluating the communication tactics applied, and assessing the effectiveness of these strategies in achieving the company's goals. A qualitative approach was used with the case study method, involving interviews and analysis of internal documents. The research results indicate that Tribunnews employs Ronald D. Smith's nine-step communication strategy model, starting from formative research to evaluation.........